Induction of Protective Immune Responses Against Schistosomiasis haematobium in Hamsters and Mice Using Cysteine Peptidase-Based Vaccine - Tallima, Hatem; Dalton, John P.; El Ridi, Rashika (Frontiers in Immunology, 2015)
One of the major lessons we learned from the radiation-attenuated cercariae (RA) vaccine studies is that protective immunity against schistosomiasis is dependent on the induction of T helper (Th)1/Th2-related immune responses. Since most schistosome larval and adult-worm-derived molecules used for vaccination uniformly induce a polarized Th1 response, it was essential to include a type 2 immune responses-inducing molecule, such as cysteine peptidases, in the vaccine formula. Here we demonstrate that a single subcutaneous injection of Syrian hamsters with 200 microg active papain 1 h before percutaneous exposure to 150 cercariae of Schistosoma haematobium led to highly significant (P < 0.005) reduction of > 50% in worm burden and worm egg counts in intestine. Immunization of hamsters with 20 microg recombinant glyceraldehyde 3-phosphate dehydrogenase (rSG3PDH) and 20 ug 2-cys peroxiredoxin-derived peptide in a multiple antigen peptide construct (PRX MAP) together with papain (20 microg/hamster) as adjuvant led to considerable (64%) protection against challenge S. haematobium infection, similar to the levels reported with irradiated cercariae. Cysteine peptidases-based vaccination was also effective in protecting outbred mice against a percutaneous challenge infection with S. haematobium cercariae. In two experiments, a mixture of Schistosoma mansoni cathepsin B1 (SmCB1) and Fasciola hepatica cathepsin L1 (FhCL1) led to highly significant (P < 0.005) reduction of 70% in challenge S. haematobium worm burden and 60% reduction in liver egg counts. Mice vaccinated with SmCB1/FhCL1/ rSG3PDH mixture and challenged with S. haematobium cercariae three weeks after the second immunization displayed highly significant (P < 0.005) reduction of 72% in challenge worm burden and no eggs in liver of 8-10 mice/group, as compared to unimmunized mice, associated with production of a mixture of type 1 and type 2-related cytokines and antibody responses.